Persepsi Masyarakat terhadap Pentingnya Pendidikan Tinggi Untuk Kaum Perempuan - Nur Annisa; Oyoh Bariah; Achmad Junaedi Sitika (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
All citizens, regardless of gender, have the right to education, including higher education. However, due to the nature of women working in the kitchen, women's higher education still overlaps. Therefore, women should be informed about higher education in society. The purpose of this study is to explain the current educational status of women in the Pakusarakan area of Karawang district, to explain public opinion about women with higher education and to explain public opinion about the,,importance,,of higher education for women. This research is a qualitative technical research. The subject of this research is a case study to the community and the data collection methods in this study are observation, interviews and documentation. Sources of data used in this study are primary and secondary data sources. The results of this study: The education level of women in Pakusarakan is mostly agricultural graduates, and women born in the 1970s and 1980s on average only completed elementary school. However, due to the development of educational facilities, young girls are currently enrolled in colleges in the Pakusarakan area. Society views women with positive education and hopes to use their,,knowledge in,,society and there are still people who consider women as women. Due to its culinary nature, it is not important to be highly educated, but to many highly educated people. What is important for women is that they will be the future educators of their children.